O rating soberano na cobertura do jornalismo econômico digital: a homogeneidade categórica dos veículos de comunicação e a homologia entre o campo econômico e o do jornalismo - Nascimento, Romário Rocha do (2021)
This dissertation sought to reflect on the process of mediatization of digital economic journalism, when reproducing the content about the Brazilian sovereign rating, issued by the Credit Rating Agencies (CRA's), Fitch, Moody's and Standards & Poor's. The research was based on the analysis of publications of the economy sections of the digital communication vehicles Folha Mercado, Estadão Economia, Reuters Market and Agência Brasil Economia, which represent the vehicles of economic coverage of the "Economy and business news" category; and also of Infomoney, Valor Econômico, Investing and Advfn, which represent the vehicles of the "Financial Market News website" category. The analysis also provided the synthetic reports of the Rating Agencies, Fitch, Moody's and Standards & Poor's, on the evaluation of the Brazilian sovereign rating. The research aimed to verify whether economic journalism produced homogeneous symbolic goods and whether economic journalists disregarded political issues when mediatizing sovereign rating ratings and outlooks for the financial market, between 2011 and 2017. Through the literature, several grounds for research were discussed: on the journalistic side, the theoretical acceptations on media effects, the social production of news, journalists and economics journalists; on the sovereign rating side, the rating standards of economic variables, the role of metrics in contemporary economics, finance, ACR's, history and their methodologies. For the research foundation, Bourdieu's theoretical conceptions of the journalism field, the economic field, symbolic products and symbolic power were discussed; for the research problem statement, the influence of economic science as the dominant economic model was highlighted. As methods of analysis, we adhered to the application of framing and voice analysis to the journalistic publications, and framing to the ACR's reports. To objectify and compare the space of the framing of the ACR's, the economic journalism and the voices, the techniques of Multiple Correspondence Analysis (MCA) and descriptive statistical analysis were adopted. In the results, it was observed that among the communication vehicles there is a categorical homogeneity, which varies from positions and oppositions of the analysis categories, that is, by distinctions of problems of economic, political, periods or by voices. A relevant result is the heterogeneity of the digital economy editorship of Estado de S. Paulo, Estadão Economia, which has dissimilar content, being opposed to other vehicles, including those of its own category. The analysis of the voices showed that the newspapers tended to mediatize, most of the time, the voices of professionals and managers of financial institutions, experts from CRA's, representatives of the government's public articulation, and economists from business entities. For depoliticization, it was observed that the vehicles do not dilute the content of the political sphere, on the contrary, it is highly diffused by economic journalism. By this same result, it was found that there is a strong level of homology between the economic field and the journalism field, that is, journalists have little modified the order imposed by the economic field